The environment (includes experiments) - Harlow, Rosie; Morgan, Sally (Kingfisher London, 2001)
An introduction to environmental science which focuses on environmental issues facing the planet and considers ways of conserving natural resources. Includes suggestions for related experiments. Suggested level: primary, intermediate